Decision-making style explains the withdrawal behavior of shy individuals: evidence from Chinese college students - Yu, Yang; Sun, Hong (Frontiers in Psychology, 2023)
Few studies have examined the mechanisms linking motivated behavior and rewardpunishment stimuli in shy individuals. This study was designed to probe these mechanisms by examining shy and non-shy college student responses to both monetary rewards and penalties in the Iowa Gambling Task (IGT). Specifically, out of the 280 undergraduates surveyed in East China, 45 participants (18 boys) identified as shy and 45 (19 boys) identified as non-shy based on their shyness questionnaire scores were selected to participate in the IGT. Results revealed that shy participants selected favorable low-risk seeking decks (deck C) more frequently and adverse highrisk seeking decks (deck B) less frequently and were more inclined to change deck selection after incurring a net loss. Furthermore, the net score of shy students was higher than that of nonshy students. Results demonstrated that shy people were the winners of IGT games, indicating that they are more likely to exhibit risk-averse behaviors when making decisions. The results are discussed from the perspective of the decision-making style and practical implications of shy individuals.